Reliability Evaluation Based on Multiple Response Surfaces Method Considering Construction Uncertainties of Cable Tension for a Hybrid Roof Structure - Sondipon Adhikari (ASCE-ASME Journal of Risk and Uncertainty in Engineering Systems, Part A: Civil Engineering, 2021)
For large-span hybrid roof structures, the construction uncertainties of cable tension usually have significant influences on the roof’s mechanical performance and should be considered in reliability evaluation. An effective approach to quantify uncertainties of cable tensions and evaluate structural reliability is proposed to carry out the studies by combining finite-element simulation with the multiple response surfaces method. Taking a hybrid roof structure with cables and steel trusses as an example, the main procedures on this issue are illustrated. First, a finite-element model is established for the hybrid roof structure considering construction deviations, such as the deviations of cable force between the design values and the real measured values. The ultimate bearing capacity of the structure is calculated for models with and without deviations, and the effects of construction deviations on structural bearing capacity are analyzed. Then, an uncertainty model of cable tension for structural reliability evaluation is proposed by establishing the statistics of initial strain in a structural analysis based on the monitored deviations. With subspace division and limit state sample (or sample pair), the multiple response surfaces method is developed to solve reliability for examples with complex failure functions. It is found that the hybrid roof structure has a high reliability index about 6.76; and the uncertainties of cable tensions have a large impact on the reliability, especially the uncertainties of the upper suspension cable tensions and the back cable tensions.